2021
DOI: 10.3390/ijms22052653
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic and Antitumor Activities of Orally Administered NAX014 Compound in a Murine Model of HER2-Positive Breast Cancer

Abstract: The natural isoquinoline alkaloid Berberine (BBR) has been shown to possess several therapeutic effects, including anticancer activity. Different BBR derivatives have been designed and synthesized in order to obtain new compounds with enhanced anticancer efficacy. We previously showed that intraperitoneal (IP) administration of the BBR-derived NAX014 compound was able to counteract HER-2 overexpressing mammary tumors onset and progression in transgenic mice. However, the IP administration was found to induce o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…In a recent study, Pierpaoli and collaborators explored the efficacy of the oral administration of a BBR derivative (NAX014) in a mouse model of HER2-overexpressing breast cancer. The authors showed no signs of toxicity after the oral administration of a high dose of the compound, suggesting its safety [56].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In a recent study, Pierpaoli and collaborators explored the efficacy of the oral administration of a BBR derivative (NAX014) in a mouse model of HER2-overexpressing breast cancer. The authors showed no signs of toxicity after the oral administration of a high dose of the compound, suggesting its safety [56].…”
Section: Discussionmentioning
confidence: 89%
“…The analogs under investigation possess aromatic groups attached to the 13-position of the parent alkaloid skeleton through a hydrocarbon linker [49]. Their effects on Wnt/β-catenin signaling [50] and on some relevant human tumor types have been reported, both in vitro [36,[51][52][53][54][55] and in vivo [41,56]. and treatment of colon cancer through the inhibition of Wnt/β-catenin signaling [40] and in exerting anticancer activity, delaying the development of MTs in transgenic mice for the HER-2/neu oncogene [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with nanotechnology, 9-O-octadecyl substituted BBR derivative induce mitochondrial apoptosis ( Song et al, 2019a ). 13-dichlorophenylalkyl BBR semisynthetic derivatives, especially 13-[3-(2,4-dichlorophenyl)propyl]-9,10-dimethoxy-5,6-dihy-drobenzo[ g ]-1,3benzodioxolo[5,6-a]quinolizinium chloride induced apoptosis in breast cancer cells, while, 13-[2-(4-chlorophenyl)ethyl]berberine iodide (NAX014) reduced HER2 overexpressing breast cancer cell migration, and intragastric administration of 20 mg/kg NAX014 in HER2/neu transgenic mice delayed the onset of mammary tumors with no negative effects on health and survival ( Pierpaoli et al, 2018 ; Pierpaoli et al, 2021 ).13-Ethylberberine induces apoptosis through the mitochondria-related apoptotic pathway in radiotherapy-resistant breast cancer cells ( Jin et al, 2019 ). 9-/13-lipophilic substituted BBR derivatives, such as 9-O-dodecyl-BBR, 13-dodecyl-BBR, and 13-O-dodecyl-BBR, show significant photocytotoxic effects on HepG2 cells and induce remarkable cancer cell apoptosis ( Lin et al, 2020 ).…”
Section: Anticancer Effect Of Bbr Derivativesmentioning
confidence: 99%
“…In particular, the readers of this Special Issue will learn about the anti-tumor activity of neosynthesized, natural, and already-available drugs that could be used as new anti-BC drugs. Indeed, the contributing authors have reported the antiproliferative activity of berberine and troglitazone derivatives, resveratrol analogs, atoquavone, clotrimazole, fenticonazole, compounds specifically targeting mitochondrial activity, and valproic acid, as well as NAMPT and carbonic anhydrase IX inhibitors [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
mentioning
confidence: 99%